Sevoflurane induces short‐term changes in proteins in the cerebral cortices of developing rats. Issue 3 (27th November 2012) - LI, Y.; LIU, C.; ZHAO, Y.; HU, K.; ZHANG, J.; ZENG, M.; LUO, T.; JIANG, W.; WANG, H.
<x xml:space="preserve">Abstract</x> Background Exposure to intravenous or inhaled anesthetic agents has potential deleterious effects on the developing brain. However, the mechanisms are not clear. Herein, we investigated protein expression changes in neonatal rat brains after exposure to sevoflurane, an inhalational anesthetic commonly used for pediatric patients. Methods Seven‐day‐old rats were treated with 1.8% sevoflurane or 30% oxygen for 4 h. Cerebral cortices were obtained at 3 h and 3 days after sevoflurane exposure for cell apoptosis detection, proteomic analysis and Western blotting. Results There was a significant increase of cleaved caspase 3 at 3 h after sevoflurane exposure. Six proteins had 1.5‐fold or higher changes in expression at 3 h after sevoflurane anesthesia as compared with sham‐treated pups. No proteins had this degree of change at 3 days after sevoflurane anesthesia. Proteins whose expression was downregulated included collapsin response mediator protein‐1 (CRMP‐1), truncated CRMP‐4, beta‐tubulin IIc and neuron‐specific class III beta‐tubulin. These four proteins are important for neuronal migration and differentiation. Adenosine triphosphate synthase beta subunit, a protein associated with energy metabolism, was also downregulated. Guanine nucleotide‐binding protein beta 1, a signaling protein, was upregulated. Sevoflurane also increased phosphorylation of glycogen synthase kinase 3β (GSK‐3β) at 3 h after anesthesia and inhibited the normal increase of GSK‐3β at 72 h after anesthesia. Conclusion These findings suggest that sevoflurane may cause short‐term neuronal apoptosis and disturbances of neuronal migration, differentiation and energy metabolism in neonatal rat brains, and that these disturbances may contribute to its neurodegenerative effects.